(untitled) (The Research of Medical Science Review, 2024)
Transcranial direct current stimulation (tDCs) is a non-invasive brain stimulation technique that involves applying a milliampere electrical current to the scalp to change cortical excitability and activity. Psychological states known as neuropsychiatric disorders which include substance abuse, depressive disorders, and schizophrenia, are marked by abnormal affective and psychological functioning. These illnesses have a significant impact on an individual's social life and functioning. For thousands of years, people have used electricity, especially from electric fish, to treat pain as well as other diseases. For neuromodulation several noninvasive methods have also been used like Transcranial electrical stimulation (TES), Electroconvulsive therapy (ECT), Transcranial alternating current stimulation (tACs), Deep brain stimulation (DBS) etc. Above mention devices are working on AC current which is not safe for human beings but tDCs device work on DC current which is safe for human beings. The objective is to design a low cost tDCs device and increase the range of current upto 4 milliampere as well as to increase the time duration of session upto 40 minutes. The working of tDCs prototype depends on a microcontroller-based embedded system and a current circuit which is used to provide the milliampere current to the patient. The programmed microcontroller is used to control the current and the sponge electrodes are placed on the head of the patients through these electrodes the current is delivered. Transcranial direct current stimulation device work on four different conditions and test the device on simulator to get the desired results. The most common problem in Pakistan is neurological and mental disorders their treatment options are less and expensive. The prototype designed is maybe a life supporting device that addresses these issues related to mental and neurological disorders. The future work is to perform clinical trials on tDCs devices and enhance its efficiency and safety.